2011
DOI: 10.1678/rheology.39.65
|View full text |Cite
|
Sign up to set email alerts
|

Topological Interaction between Loop Structures in Polymer Networks and the Nonlinear Rubber Elasticity

Abstract: We numerically examine the nonlinear rubber elasticity of topologically constrained polymer networks. We propose a simple and effective model based on Graessley and Pearson's topological model (GP model) for describing the topological effect. The main point is to take account of a nonequilibrium effect in the synthesis process of the polymer network. We introduce a new parameter γ to describe entropic contributions from the entanglement of polymer loops, which may be determined from the structural characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In the case of melt‐cured networks with many entanglement couplings, the I 2 term has often been attributed to the entanglement effect, but this is not so in the case of Tetra‐PEG gels. In addition to the trapped‐entanglement effect, several concepts such as nematic interaction, excluded volume effect and topological interaction have been proposed so far as the origin of the deviation from classical theories. At present, it is difficult to evaluate unambiguously the concept that accounts for the present results because most of these concepts involve phenomenological model parameters.…”
Section: Tetra‐peg Hydrogelsmentioning
confidence: 99%
“…In the case of melt‐cured networks with many entanglement couplings, the I 2 term has often been attributed to the entanglement effect, but this is not so in the case of Tetra‐PEG gels. In addition to the trapped‐entanglement effect, several concepts such as nematic interaction, excluded volume effect and topological interaction have been proposed so far as the origin of the deviation from classical theories. At present, it is difficult to evaluate unambiguously the concept that accounts for the present results because most of these concepts involve phenomenological model parameters.…”
Section: Tetra‐peg Hydrogelsmentioning
confidence: 99%
“…The second approach is the topological interactions between loop structures in polymer networks. [61][62][63][64] They assumed the ringshaped structures or loops as structural elements of a crosslinked network, and theoretically considered the elastic effects originating from the constraints that the topologies of the J. Chem. Phys.…”
Section: Conjecture On the Origin Of The Cross Effect Of Strainsmentioning
confidence: 99%
“…Hirayama and Tsurusaki showed that such topological effect results in an explicit cross-effect of strains even for the networks without entanglement loops. 64 The third approach considers the excluded volume effect as the source of interchain and intrachain interactions. 65 These interactions are pronounced in the high concentration region, and transmit the tension among the chains, resulting in a finite cross-effect.…”
Section: Conjecture On the Origin Of The Cross Effect Of Strainsmentioning
confidence: 99%
“…Furthermore, there are many interesting topics related to the topological effects of ring polymers: the probability of forming a local knot in a random polygon [ 111 , 112 ], flat knots (i.e., knotted ring polymers in two dimensions) [ 113 , 114 ], the mean square radius of gyration of ring polymers in melt [ 115 , 116 , 117 , 118 , 119 ], the minimal step number of a lattice knot [ 120 , 121 ], the relaxation dynamics of a knotted ring polymer in solution [ 122 ], etc. [ 123 , 124 ].…”
Section: Introductionmentioning
confidence: 99%